Carbon ion radiotherapy triggers immunogenic cell death and sensitizes melanoma to anti-PD-1 therapy in mice. (31st December 2022) - Zhou, Heng; Tu, Chen; Yang, Pengfei; Li, Jin; Kepp, Oliver; Li, Haining; Zhang, Liying; Zhang, Lixin; Zhao, Yang; Zhang, Tianyi; Sheng, Chengyan; Wang, Jufang
ABSTRACT: Carbon ion radiotherapy (CIRT) is an emerging type of radiotherapy for the treatment of solid tumors. In recent years, evidence accumulated that CIRT improves the therapeutic outcome in patients with otherwise poor response to immune checkpoint blockade. Here, we aimed at identifying the underlying mechanisms of CIRT-induced tumor immunogenicity and treatment efficacy. We used human U2OS osteosarcoma cells for the in vitro assessment of immunogenic cell death and established several in vivo models of melanoma in mice. We treated the animals with conventional radiation, CIRT, PD-1-targeting immune checkpoint blockade or a sequential combinations of radiotherapy with checkpoint blockade. We utilized flow cytometry, polyacrylamide gel electrophoresis (PAGE) and immunoblot analysis, immunofluorescence, immunohistochemistry, as well as enzyme-linked immunosorbent assays (ELISA) to assess biomarkers of immunogenic cell death in vitro. Treatment efficacy was studied by tumor growth assessment and the tumor immune infiltrate was analyzed by flow cytometry and immunohistochemistry. Compared with conventional radioimmunotherapy, the combination of CIRT with anti-PD-1 more efficiently triggered traits of immunogenic cell death including the exposure of calreticulin, the release of adenosine triphosphate (ATP), the exodus of high-mobility group box 1 (HMGB1) as well as the induction of type-1 interferon responses. In addition, CIRT plus anti-PD-1 led to an increased infiltration of CD4 +, and CD8 + lymphocytes into the tumor bed, significantly decreased tumor growth and prolonged survival of melanoma bearing mice. We herein provide evidence that CIRT-triggered immunogenic cell death, enhanced tumor immunogenicity and improved the efficacy of subsequent anti-PD-1 immunotherapy.